2019
DOI: 10.1088/1757-899x/603/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Data-Collection Methods for Thermal Comfort Assessment in Tropical Countries

Abstract: Thermal comfort in the built environment is one of the most defining parameters influencing energy use, environmental quality, and occupant satisfaction; therefore, it is currently receiving a great deal of academic attention. Unfortunately, there is still a pronounced lack of research in this area within developing countries in tropical regions, which are becoming increasingly urbanised and where mechanical air conditioning demands are rising dramatically. Many of these countries are adopting thermal comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Simulaciones ambientales aplicadas a la selección de materiales para el diseño de alojamientos temporales en climas tropicales 2014 0 0 Girardot, Bogotá [26] Calidad de vida en la vivienda social de San Andrés, Colombia, mediante la gestión bioclimática de flujos de aire 2015 0 0 San Andrés [27] Ventajas del uso de fachada ventilada en Girardot (Colombia). Un complemento tecnológico a fachadas modulares industrializadas 2015 0 0 Girardot [28] Evaluación de las condiciones térmicas ambientales del área de producción en una panadería en Cereté (Córdoba) 2016 0 0 Cereté [29] Ventilación pasiva y confort térmico en vivienda de interés social en clima ecuatorial 2017 0 0 Cali [30] Evaluación del confort térmico en una institución educativa en la ciudad de Barranquilla 2018 0 0 Barranquilla [50] The development of data-collection methods for thermal comfort assessment in tropical countries 2019 0 0 Bogotá [51] Out of the 25 documents selected during the second search, there were two PhD theses, seven Master thesis, one specialisation work, three undergraduate final projects, and 12 unpublished studies (Table 5). The total sample of 65 documents was examined regarding the volume, origin, impact, focus, and content of past and current research projects and documentation on thermal comfort in Colombia.…”
Section: Article Other Journalsunclassified
See 1 more Smart Citation
“…Simulaciones ambientales aplicadas a la selección de materiales para el diseño de alojamientos temporales en climas tropicales 2014 0 0 Girardot, Bogotá [26] Calidad de vida en la vivienda social de San Andrés, Colombia, mediante la gestión bioclimática de flujos de aire 2015 0 0 San Andrés [27] Ventajas del uso de fachada ventilada en Girardot (Colombia). Un complemento tecnológico a fachadas modulares industrializadas 2015 0 0 Girardot [28] Evaluación de las condiciones térmicas ambientales del área de producción en una panadería en Cereté (Córdoba) 2016 0 0 Cereté [29] Ventilación pasiva y confort térmico en vivienda de interés social en clima ecuatorial 2017 0 0 Cali [30] Evaluación del confort térmico en una institución educativa en la ciudad de Barranquilla 2018 0 0 Barranquilla [50] The development of data-collection methods for thermal comfort assessment in tropical countries 2019 0 0 Bogotá [51] Out of the 25 documents selected during the second search, there were two PhD theses, seven Master thesis, one specialisation work, three undergraduate final projects, and 12 unpublished studies (Table 5). The total sample of 65 documents was examined regarding the volume, origin, impact, focus, and content of past and current research projects and documentation on thermal comfort in Colombia.…”
Section: Article Other Journalsunclassified
“…During the review of the selected documentation, recurrent themes were identified concerning limitations of the assessment models. Various studies emphasised on the inadequacy of mainstream evaluation standards applied in Colombia and the need to confirm these models with further post-occupancy studies and standardised fieldwork data [21,51]. For example, a study in three office buildings in Bogotá compared different assessment models to assess three ventilation scenarios (natural ventilation, mechanical ventilation, and mixed mode), via occupant surveys and simultaneous environmental measures [15].…”
Section: Main Findings From the Published Documentsmentioning
confidence: 99%